DESIGN AND MYOELECTRIC CONTROL OF AN ACTIVE ORTHOSIS DEVICE USING FINITE STATE MACHINE ALGORITHM - Ulkir, Osman; Akgun, Gazi; Toptas, Ersin; Kaplanoglu, Erkan (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This paper presents a novel myoelectric controlled active hip-knee-ankle-foot orthosis (A-HKAFO) designed to assist lower limb disorders. The proposed orthosis device2 consists of a polypropylene shell and a metal hinge joint, is designed to help patients during gait rehabilitation after neurological injury, and assist people who have difficulty walking3 due to obesity, sports injuries. The system also can use4 for studying human gait biomechanics5. A myoelectric control law strategy is proposed using a finite state machine (FSM) method. The algorithm is activated by users’ intend to forward or backward stepping6. The electromyogram (EMG) signals from lower limb7 and device motion data were8 used for the control of A-HKAFO. In order to determine the last location of the user after movement, physical feedback is utilized from the mechanical system.